I'wak alternative strategies for subsistence : a micro-economic study : the Iwak of Boyasyas, Nueva Vizcaya, Philippines - Peralta, Jesus T. (Anthropological papers / National Museum, 1982)
Purpose: Serves as an anthropological study of I'wak, an indigenous group of people living in Nueva Vizcaya province.